Bacteria Display Differential Growth and Adhesion Characteristics on Human Hair Shafts - Kerk, Swat Kim; Lai, Hui Ying; Sze, Siu Kwan; Ng, Kee Woei; Schmidtchen, Artur; Adav, Sunil S. (Frontiers in Microbiology, 2018)
Apart from the skin surface, hair represents a significant tissue component with a capacity of bacterial interactions. New information can be obtained about hair function through the characterization of bacterial adherence, colonization, and responses to hair shafts per se. In this proof-of-principle study, we examine the growth kinetics of Gram-positive Staphylococcus aureus and S. epidermidis, and Gram-negative Pseudomonas aeruginosa and Escherichia coli in the presence of human hair shafts. We explore the ability of these bacteria to adhere to and colonize hair shaft surfaces, as well as the resulting impact on the hair’s surface morphology. We show that hair shafts inhibit the growth of Gram-positive S. aureus and S. epidermidis, while the growth kinetics of P. aeruginosa and E. coli remain unaffected. Scanning electron microscope analysis and steeping studies show that P. aeruginosa and E. coli to adhere to and colonize on human hair shafts without significantly affecting the hair shaft’s surface morphology. P. aeruginosa produced a substantial amount of biofilm on the hair shaft surfaces, while E. coli specifically inhabited the edges of the cuticle scales. Taken together, our results demonstrate differences in bacterial responses to human hair shafts, which may provide novel insights into hair and scalp health.